AdaBoost for Text Detection in Natural Scene - Jung-Jin Lee; Pyoung-Hean Lee; Seong-Whan Lee; Yuille, A.; Koch, C. (2011 International Conference on Document Analysis and Recognition, 2011)
Detecting text regions in natural scenes is an important part of computer vision. We propose a novel text detection algorithm that extracts six different classes features of text, and uses Modest AdaBoost with multi-scale sequential search. Experiments show that our algorithm can detect text regions with a f= 0.70, from the ICDAR 2003 datasets which include images with text of various fonts, sizes, colors, alphabets and scripts.